Factors Affecting Use of Formal Agricultural Credit among Smallholder Farmers in Western Nepal - Mishra, B.P. (International Journal of Social Sciences and Management, 2021)
Formal agricultural credit is important for sustainable development of agriculture sector and national economy, particularly in developing countries. Yet, many smallholder farmers lack participation in formal credit market. An investigation was done during 2019 in two main agro-ecological regions (hill and terai region) of western Nepal. Probit model was used to identify the factors affecting the use of formal agricultural credit among smallholder farmers. The results revealed that use of formal agricultural credit increases with age, education, commercial nature of production, and collateral availability, and decreases with number of adult in household, farming experience and farm size. The study concludes with key policy recommendations. Int. J. Soc. Sc. Manage. Vol. 8, Issue-4: 457-462.